Management of spine-related problems following sport injuries: a review article - Roohollahi F. (Asian Journal of Sports Medicine, 2022)
Context: Athletes have routine activity programs, and better physical health is expected among them. There is limited information about the connection between athletes' injuries during sports activity and their future health status. Objectives: The prevalence of spine changes related to sports activities and what risk factors were associated with these events in athletes. Method: SCOPUS, EMBASE, and Web of Science were used for article searching. Results: Sports injuries in sports happen frequently. Our data is limited to introducing sports with the highest risk of injury. A history of sports injury, an intense training program, and years of sports activities are factors predicting injury. It has been seen that former top male athletes have more activity than age-matched control individuals. Conclusions: Spinal injury management in athletes needs a proper diagnosis, work-up, and complex rehabilitation plans; otherwise, it can lead to spinal complaints in the future. Rest, appropriate analgesia, and rehabilitation are the three main primary treatments. The usage of orthoses is not recommended for these injuries in general.